1975
DOI: 10.1111/j.1432-1033.1975.tb09821.x
|View full text |Cite
|
Sign up to set email alerts
|

Action of Rheumatoid Synovial Collagenase on Cartilage Caollagen

Abstract: The action of purified rheumatoid synovial collagenase on purified cartilage collagen, U~( I I )~, in solution at 25 "C has been characterised. The enzyme attacked cartilage collagen in solution producing a 5 8 % reduction in specific viscosity and resulting in the appearance of two reaction products which represented approximately three-quarter and one-quarter fragments of the intact molecule as shown by disc electrophoresis in polyacrylamide gels containing sodium dodecyl sulphate. The a-chain fragments whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…This is identical with the substrate-specificity exhibited by rheumatoid synovial collagenase (Woolley et al, 1975a). The inability to degrade basement-membrane collagen type IV appears to be a property common to the vertebrate collagenases, which act on the interstitial collagens, types I, II and III (Liotta et al, 1979;Woolley et al, 1978).…”
Section: Discussionsupporting
confidence: 62%
“…This is identical with the substrate-specificity exhibited by rheumatoid synovial collagenase (Woolley et al, 1975a). The inability to degrade basement-membrane collagen type IV appears to be a property common to the vertebrate collagenases, which act on the interstitial collagens, types I, II and III (Liotta et al, 1979;Woolley et al, 1978).…”
Section: Discussionsupporting
confidence: 62%
“…Bonds of Gly-Ile or Gly-Leu were also cleaved in collagen type II and type III and the specificity of cleavage was the same for these collagens as it was for type I collagen (Miller et al, 1976a). However, the rate of cleavage of type II collagen was approximately one-fifth to one-sixth that of collagen type I or type HI (McCroskery et al, 1975;Woolley et al, 1975a;Miller et al, 1976a;see Fig. 39).…”
Section: Fig 37mentioning
confidence: 91%
“…In TC B (3), the N ' -N ' terminal junction corresponds to the region between bands 41 and 42 shown in collagen (2). Reproduced with permission fromWoolley et al (1975a).copy in SLS aggregates, the position of cleavage of either type I or type II collagen by vertebrate collagenase can be assigned to the inte rband region between bands 41 and 42, approximately 2250 Â from the amino terminus of the helical part of the molecule (Leibovich and Weiss, 1973; Woolley et al, 1975a; see Fig…”
mentioning
confidence: 97%
“…Firstly, collagenase is elaborated by various normal and neoplastic cells; whereas its limited production by cells in normal tissues suggests a role in collagen remodeling processes, its more frequent occurrence in malignant tissues suggests an important role in pathological collagen resorption. Studies on the susceptibility of the various genetic types of collagens to mammalian collagenase have shown that type III collagen is cleaved at a rate comparable to that of type I collagen, but at approximately five times the rate measured for type II collagen (104,110,111). Type IV and type V collagens are not susceptible to attack by mammalian collagenase, but are each cleaved by specific neutral metalloproteinases (70,75,83).…”
Section: B Tumor-derived Proteolytic Enzymesmentioning
confidence: 99%